Surprising pressure-induced magnetic transformations from helimagnetic order to antiferromagnetic state in NiI2 - Qiye Liu; Wenjie Su; Yue Gu; Xi Zhang; Xiuquan Xia; Le Wang; Ke Xiao; Naipeng Zhang; Xiaodong Cui; Mingyuan Huang; Chengrong Wei; Xiaolong Zou; et al. (Nature Communications)
Abstract Interlayer magnetic interactions play a pivotal role in determining the magnetic arrangement within van der Waals (vdW) magnets, and the remarkable tunability of these interactions through applied pressure further enhances their significance. Here, we investigate NiI2 flakes, a representative vdW magnet, under hydrostatic pressures up to 11 GPa. We reveal a notable increase in magnetic transition temperatures for both helimagnetic and antiferromagnetic states, and find that a reversible transition between helimagnetic and antiferromagnetic (AFM) phases at approximately 7 GPa challenges established theoretical and experimental expectations. While the increase in transition temperature aligns with pressure-enhanced overall exchange interaction strengths, we identify the significant role of the second-nearest neighbor interlayer interaction $${J}_{2}^{\perp }$$ J 2 ⊥ , which competes with intra-layer frustration and favors the AFM state as demonstrated in the Monte Carlo simulations. Experimental and simulated results converge on the existence of an intermediate helimagnetic ordered state in NiI2 before transitioning to the AFM state. These findings underscore the pivotal role of interlayer interactions in shaping the magnetic ground state, providing fresh perspectives for innovative applications in nanoscale magnetic device design.